KARAKTERISASI ISOLAT RHIZOCTONIA MIKORIZA PADA ANGGREK PHALAENOPSIS AMABILIS - Soelistijono Soelistijono; DWI SISILO UTAMI; Achmadi Priyatmojo (JURNAL ILMIAH AGRINECA, 2012)
Mycorrhizal Rhizoctonia is a fungus that capable to associate with Phalaenopsis amabilis orchid. This study was aimed to characteristic mycorrhizal Rhizoctonia that associated with P. amabilis orchid in morphology. The results showed that colony colour, cell lenght and nucleus number a several isolates of mycorrhizal Rhizoctonia on P. amabilis had no differences, but had differences on cell thickness and isolate grouping based on hyphal anastomosis test